If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -1y + -2z = 2 Solving x + -1y + -2z = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. x + -1y + y + -2z = 2 + y Combine like terms: -1y + y = 0 x + 0 + -2z = 2 + y x + -2z = 2 + y Add '2z' to each side of the equation. x + -2z + 2z = 2 + y + 2z Combine like terms: -2z + 2z = 0 x + 0 = 2 + y + 2z x = 2 + y + 2z Simplifying x = 2 + y + 2z
| 110-2x=180 | | -2(7k+4)=-40-6k | | abc+4b=9d | | d^2+14d+13=1 | | d^2+14d+13=-1 | | 3x+4+7x=5(2x+1) | | 5n-29=-(-1+5n) | | 500*1.05=600 | | 3r+4=r+2(-r+8) | | 4x=4-1 | | n+10(5)=9-n | | x+82+x+75=41 | | 5x-8(x+5)=1.44-3x | | 4=4x-1 | | x+135+x+35=20 | | -3+5(4+6n)=107 | | 4-6(k+7)=5k+17 | | p-6=3(p-4) | | 8+6(t+2)=32 | | 8-6m=26 | | 8m-7(3-5m)=280 | | -12-2k=-2(k+4) | | x+135+20=x+35 | | 3(x+6)=221 | | x+40+2x-10=180 | | 1.4b+10=18 | | 34+8m=6(3m+1)-3m | | -4(2x-1)=2(3x+2)-14x | | 2a-6+5a=3-a+7 | | 3+7(-3n+6)=-4n-6 | | -6(z-2)=3 | | 17+(-3x)=14 |